Post Hoc Analyses of Data from a 90-Day Clinical Trial Evaluating the Tolerability and Efficacy of Tapentadol Immediate Release and Oxycodone Immediate Release for the Relief of Moderate to Severe Pain in Elderly and Nonelderly Patients - Gary Vorsanger; Jim Xiang; David Biondi; David Upmalis; Jacqueline Delfgaauw; René Allard; Bruce Moskovitz (Pain Research and Management)
OBJECTIVE: To evaluate the tolerability and efficacy of tapentadol immediate release (IR) and oxycodone IR for relief of moderate to severe pain in elderly and nonelderly patients.